Dynamic Network Scheduler for Customized Aperiodic Communication in Networked Control System - Abdul Kalam Azad, S. M.; Srinivasan, K. (Automatic control and computer sciences, 2021)
The optimization in the configuration of network communication with time delays among field devices is a major challenging task of a networked control system (NCS). In view with the network-based model of literature, the present paper introduces the dynamic network scheduler to customize the aperiodic time delay for optimal bandwidth allocation of the network. This is achieved with the following three objectives: (a) classification of data packets among periodic and aperiodic communication using support vectors; (b) deciding the bandwidth associated with the priority weightage for aperiodic data packets; (c) simulation for fairness of NCS with dynamic network scheduler switching integrated the weighted fair queuing algorithm. The outcome of proposed dynamic network scheduler is compared with the network model of literature for reduced and bounded delays of aperiodic communication in NCS.